Elaboração e caracterização de leite fermentado caprino “tipo iogurte” sabor goiaba com potencial probiótico - Cavalcanti, Mayra da Silva (2016)
The use of goat milk in dairy products formulation is being performed instead of cow milk, some features, including the present lower incidence of allergies. The production of fermented milk, yoghurt type, goats with the addition of probiotic cultures and fruit for saborizar the product can potentiate the beneficial health effects, and thus, the demand for this product by the consumer. This study was developed in order to prepare and characterize the technological, physical, physico-chemical, microbiological, rheological and sensory of a fermented goat added jelly Guava and probiotic cultures. The effect of the addition of probiotic lactic acid bacteria cultures on the quality characteristics of fermented milks were evaluated at the times 1, 7, 14 and 21 days, given the following treatments: CI (conventional yoghurt - control), containing the starter culture comprising Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus; ILA containing the probiotic microorganism Lactobacillus acidophilus, co-culture with the starter; ILP, comprising the probiotic Lactobacillus casei subsp. paracasei, in addition to the starter culture; and IBB containing probiotic Bifidobacterium animalis subsp. lactis in combination with a starter culture. All fermented milks tested showed good results as to the technological characteristics without undergoing syneresis, with good stability and high capacity of water retention. Samples slightly acidified during shelf life, perceived characteristic and well accepted in the sensory test, with notes whose hedonic terms ranged from "like slightly" and "liked". In general, it was observed that the addition of probiotic strains in the preparation of fermented milks did not influence the physical and physicochemical characteristics of the same (p> 0.05), noting only a reduction (p <0.05) the ash content in the sample IBB during refrigerated storage. The apparent viscosity of the samples remained high during the storage time, with greater influence (p <0.05) of the probiotic Lactobacillus casei subsp. paracasei. Thus, it was found that the preparation of a fermented milk with added guava jelly and probiotics is presented as a product with potential for investment in the dairy industry with functional properties, whose microbiological, technological, rheological, nutritional and sensory qualities were satisfactory.